CHARACTERISTICS OF FAMILY BUSINESSES IN THE CZECH REPUBLIC - Machek, Ondrej; Hnilica, Jiri; Brabec, Martin (European Scientific Journal, ESJ, 2014)
Family businesses are often considered to be different from non-family businesses because they are led or owned by family members whose aim is to continue the activities of their companies across multiple generations. According to the existing research, family businesses seem to outperform non-family businesses in terms of efficiency and financial performance. However, in the Czech Republic, the question of family business has been neglected. In this paper, we deal with basic characteristics of family firms in the Czech Republic. We also assess their financial performance and compare it with other firms using return on assets, return on equity, return on sales and labor productivity. The results are multivalent. Family businesses outperform other firms in terms of return on assets and return on equity, but other firms are more efficient in terms of return on sales and labor productivity.